(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This research paper tries to observe the narrative by political parties and how along this premise they have affected the fabric of systemic functioning on both State and Central level of governance. Specifically, in the case of inter-state water disputes where the public sentiment in general has been skewed and distorted for the benefit of political consolidation. Within this sphere of socio-political discourse, the paper will aim to unearth various possibilities, commotion and after-effects that have denied people of their rights. In short, how political maneuvering has undermined the greater good of people in water governing paradigm and resulted in misery for those who are involved in the dispute.